EFFECTS OF KNEE OSTEOARTHRITIS THERAPY BY PLATELET RICH PLASMA IN VO TRUONG TOAN HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Aim: (1) Evaluation results on VAS and KOOS scores after 12 months of treatment of osteoarthritispatients with platelet-rich plasma (PRP) therapy; (2) Evaluation results on ultrasonography and MRIafter 12 months of treatment of osteoarthritis patients with platelet-rich plasma (PRP) therapy.Subject and Method: Intervention study on 40 patients diagnosed with stage 2 and 3 osteoarthritisaccording to Kellgren and Lawrence, who were intervened by PRP. Evaluation on clinical, ultrasoundand magnetic resonance after 12 months of follow-up.Result: VAS score of the patients before the intervention was 6.53±1.81, after 12 months of theintervention it was 3.93±2.74, KOOS score of the patients before the intervention was 46.27±13, 62,after 12 months of intervention was 83.09±13.14 (P
Keywords: Knee osteoarthritis, platelet-rich plasma, PRP.